Association between knee extensor force steadiness and postural stability against mechanical perturbation in patients with Parkinson's disease. (June 2022) - Tajitsu, Hirotsugu; Fukumoto, Yoshihiro; Asai, Tsuyoshi; Monjo, Hiroki; Kubo, Hiroki; Oshima, Kensuke; Koyama, Shota
Abstract: Objective: Lower extremity force steadiness has been shown to decrease with aging and neuromotor dysfunction and to be associated with physical function and fall. Although patients with Parkinson's disease (PD) experience decreased force steadiness, whether the extent of force steadiness differs according to target force or whether this steadiness is associated with postural control remain unclear. Therefore, this study aimed to compare the force steadiness while steadily exerting low and moderate levels of knee extensor force between individuals with and without PD and to examine the association between force steadiness and postural instability against mechanical perturbation in PD. Methods: A total of 33 patients with PD (mean age, 71.7 years) and 33 healthy controls (72.2 years) participated in this study. Participants with PD were classified into postural stability or instability groups based on the Movement Disorder Society-sponsored revision of the Unified Parkinson's Disease Rating Scale motor exam item 12. Participants performed steady task of the knee isometric extension at two levels (10% and 50% of maximal voluntary contraction [MVC]). Results: Force steadiness at 10% MVC was lower in postural instability group than that in the control and postural stability groups (P < 0.05) after adjusting for age, sex, and body mass index, whereas it was not significantly different at 50% MVC among the three groups. Discussion: These results suggest that the knee extensor force steadiness is affected in patients with PD having postural instability against mechanical perturbation during low intensity force exertion and is not affected regardless of the presence of postural instability during moderate intensity force exertion.